Network centrality and innovation performance: the role of formal and informal institutions in emerging economies. Issue 6 (1st July 2019) - Wang, Haifeng; Zhao, Yapu; Dang, Beilei; Han, Pengfei; Shi, Xin
Abstract : Purpose: The impact of network centrality on innovation performance is inconclusive. The purpose of this paper is to examine how formal and informal institutions affect the influence of network centrality on firms' innovation performance in emerging economies by integrating social network theory and institutional theory. Design/methodology/approach: Multisource and lagged data from 234 technology-based entrepreneurial firms listed on the Chinese Growth Enterprise Market were leveraged to test a proposed research model. Findings: Results suggest that formal institutions (marketization) positively moderate the relationship between network centrality and innovation performance, whereas informal institutions (social cohesion) negatively moderate this relationship. Moreover, formal and informal institutions have a strong joint impact on such relationship, that is, the effect of network centrality on innovation performance is most positive when marketization is high and social cohesion is low. Originality/value: This empirical research provides new insights into whether and how firms can grasp the innovation benefits of network centrality by exploring institutional contingencies. It further sheds on light the scope of the network centrality–innovation issue by extending its research context to Chinese entrepreneurial firms.